Case Report: Multimodality imaging of a congenital ventricular septal aneurysm complicated by biventricular myocardial non-compaction in a child - Zhou, Jie; Chen, Jiao (Frontiers in Pediatrics, 2025)
Congenital ventricular aneurysm is a rare malformation affecting all cardiac chambers, and is most frequently observed in the left ventricle. Congenital ventricular aneurysm is characterized by localized bulges in the ventricular wall, typically distinct from the normal myocardium, and it shows akinesia or dyskinesia. Using multimodality imaging, we diagnosed a case of ventricular septal aneurysm complicated by biventricular myocardial non-compaction in a child. After excluding various potential causes, we considered a congenital developmental abnormality as the most likely pathogenic factor.